TEACHING MATERIALS FOR WRITING NARRATIVE TEXT WITH COMIC STRIPS - Dila Fitri; Rahayu Apriliaswati; Yanti Sri Rezeki (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2024)
This research is in the form of teaching materials; is teaching material for writing comic strip narrative texts. The aim is to design a sample of teaching materials for narrative writing for tenth grade high school students. The author applies ADDIE as the procedure. This development research was carried out to produce innovative teaching materials. The product designed is combined with comic strip media. The stories used in this product focus on legends taken from West Kalimantan folklore. Examples of teaching materials consist of materials, several assignments, and assessments that are linked to the syllabus and learning objectives. The author uses expert validation to validate the usefulness of the material. It was revealed that the product interpretation results were very good. In addition, samples of teaching materials designed based on observations of English textbooks, syllabi and teacher validation show that additional teaching materials can be used as teaching materials for narrative writing texts, especially for high school students.